Analisis Kritis Prospek Pemerintahan Efektif Pada Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu Kabupaten Ogan Komering Ilir - Pebriadi, Elpis; Putra , Raniasa (Syntax Literate, 2025)
This study analyzes the prospects for effective governance at the Investment and One-Stop Integrated Services Agency (DPMPTSP) of Ogan Komering Ilir (OKI) Regency using qualitative case study methods and document analysis. DPMPTSP demonstrates remarkable procedural effectiveness, with performance targets achieving more than 650% for licensing services and 438% for investment realization by 2024, as well as consistently achieving a Public Satisfaction Index (IKM) of "GOOD" to "VERY GOOD." However, its substantive effectiveness still faces challenges, such as low public assessments of apparatus competence and complaint handling, and a gap between massive investment and local economic impact. DPMPTSP's prospects are determined by political commitment in the Regional Medium-Term Development Plan (RPJMD) and inhibiting factors such as gaps in human resource capacity, a non-transformative bureaucratic culture, and digital exclusion in services. Strategic recommendations cover three areas: (1) developing human resource capacity with a focus on analysis and facilitation, (2) establishing a proactive unit for investment and MSME assistance, and (3) strengthening the feedback system for continuous service improvement.